Studi Tafsir Nusantara: Tafsir al-Huda, Tafsir Qur’an Basa Jawa Karya Jend. Purn. Drs. H. Bakri Syahid al-Yogjawy - Neny Muthiatul Awwaliyyah (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2021)
This research focuses on the commentary written by a person with the rank of colonel and involved in the military and political world. Bakri Shahid's military, academic, and ethnic backgrounds influenced his interpretation of Tafsir al-Huda. The data mining technique in this study uses a qualitative approach using library research techniques, namely by collecting data through readings and literatures that are related to the discussion. The writing method used in this research is descriptive-analytic method. The primary source in writing this article is the Tafsir of the Jawian Qur'an by Brigadier General (Purn.) Drs. H. Bakri Shahid and other literature relevant to the article, especially regarding methods and patterns in interpretation. From the results of the study, it is known that the interpretation written with the interpretation model is in the form of footnotes and uses Javanese language that is smooth and thick with Javanese culture in its interpretation.